2021
DOI: 10.1177/13691481211048502
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of poor representation: How voter–party incongruence curbs affective polarisation

Abstract: Research on the relationship between ideology and affective polarisation highlights ideological disagreement as a key driver of animosity between partisan groups. By operationalising disagreement on the left–right dimension, however, existing studies often overlook voter–party incongruence as a potential determinant of affective evaluations. How does incongruence on policy issues impact affective evaluations of mainstream political parties and their leaders? We tackle this question by analysing data from the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…Affective polarization affects the weakening of partisan identity, and in recent years, there have been partisans who dislike their own party [21]. In the study by Marchal [22], it is shown that incongruence with one's own party, especially on prominent personal issues, curbs affective polarization by fostering positive evaluations of the opposition and negative evaluations from within the party. Individuals distance themselves from supporters of opposing political parties when they perceive a threat to their ingroup and react with anger [23].…”
Section: Affective Polarizationmentioning
confidence: 99%
“…Affective polarization affects the weakening of partisan identity, and in recent years, there have been partisans who dislike their own party [21]. In the study by Marchal [22], it is shown that incongruence with one's own party, especially on prominent personal issues, curbs affective polarization by fostering positive evaluations of the opposition and negative evaluations from within the party. Individuals distance themselves from supporters of opposing political parties when they perceive a threat to their ingroup and react with anger [23].…”
Section: Affective Polarizationmentioning
confidence: 99%